Mitigasi Dampak Negatif Sosial Media terhadap Penjualan Suatu Produk - Pujianto, Anang Bambang; Sarifiyono, Aggi Panigoro; Purnama, Susan; Sinaga, Johnson (Ma'soem University, 2025)
The development of social media has had a significant impact on product marketing and sales. While social media provides opportunities for companies to increase brand exposure and expand market reach, it also serves as a source of negative information that can damage brand image and reduce sales performance. This study aims to analyze mitigation strategies for addressing the negative effects of social media on product sales. A quantitative approach was employed using a survey of 100 respondents, analyzed with multiple linear regression. The results show that negative social media exposure decreases sales by 1.85%, whereas mitigation strategies increase sales by 2.14%. The coefficient of determination (R²) of 0.72 indicates that 72% of the variation in sales changes can be explained by negative social media effects and mitigation strategies. Furthermore, t-tests and F-tests confirm that both variables have a significant impact on sales performance. These findings demonstrate that structured mitigation strategies are effective in helping companies counter the negative impact of social media and maintain sales stability.